Digital Tools and the Derailment of Iceland's New Constitution - Thorvaldur Gylfason; Anne Meuwese (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper maps the use of digital tools in the Icelandic constitutional revision process of 2011 and discusses its aftermath in subsequent years. Although causal links between the digital elements of the process and the content and fate of the constitutional bill are impossible to establish, an analysis of the Icelandic constitution-writing efforts as `digital democracy' reveals some important lessons. High-quality input into constitution-making processes through digital participation is possible, but the very threat of this to vested institutional interests also makes consensus on and enforcement of the `rules of the game' of paramount importance.
Keywords: K10; 330; digital tools; democracy; constitutions; Iceland